2014
DOI: 10.1002/anie.201408810
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Fluorescent Probe to Amyloid‐β to Reveal Kinetic Insights into Its Interactions with Copper(II)

Abstract: The kinetics of the interactions between amyloid‐β (Aβ) and metal ions are crucial to understanding the physiological and pathological roles of Aβ in the normal brain and in Alzheimer’s disease. Using the quenching of a fluorescent probe by Cu2+, the mechanism of Aβ/Cu2+ interactions in physiologically relevant conditions has been elucidated. Cu2+ binds to Aβ at a near diffusion‐limited rate, initially forming component I. The switching between component I and II occurs on the second timescale, with a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 37 publications
7
103
0
Order By: Relevance
“…[14] It was established that Cu II initially binds to Ab as component I, which then undergoes ac onformational change to component II, and that metal-ion-bridged dimers (Ab·Cu·Ab)a re formed mainly by component I. These observations are all in qualitative agreement with the model proposed in this work.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…[14] It was established that Cu II initially binds to Ab as component I, which then undergoes ac onformational change to component II, and that metal-ion-bridged dimers (Ab·Cu·Ab)a re formed mainly by component I. These observations are all in qualitative agreement with the model proposed in this work.…”
supporting
confidence: 85%
“…It seems likely that Cu II complexesw ith small-molecule ligands affect the binding of Cu II to Ab in vivo. Finally, Ying andc o-workers [14] assume that the Ab·Cu·Ab complex is on-pathway in the aggregation process, but this is not substantiated by experimental data on aggregation.C onversely, with the current work we cannot exclude the possibility that their assumption is correct,a lthough the simplest model (Figure 4) given the data presentedh ere indicates that it is offpathway.T he important question of which dimerics pecies is most aggregation pronei ss till to be elucidated.…”
mentioning
confidence: 99%
“…However,d ue to the high amide pK a values (> 15) they are not measurable by experimental titration. [31] Nevertheless,b ased on the discussion presented above,o ne may propose that positivelyc harged and/or Hbond donor side chains could interactw ith the amide carbonyl oxygen, hence decreasing the peptide group pK a ( Figure 2C). Thus, side chainsl ike Lysa nd Arg at positions 1a nd 2s hould increaset he affinity of Cu II .I nc ontrast, negatively charged and H-bond acceptors could interact (through H-bonding) with the HÀNo ft he amide bond,i ncreasing its pK a ( Figure 2D), and consequently decreasing its affinity for Cu II .F or example, Asp is more efficient than Glu in this respect, as the H-bond created forms a7 -membered versusa9-membered ring.…”
Section: Influence Of Xxx/zzzmentioning
confidence: 90%
“…As indicated above, the p K a of the coordinating peptide bond nitrogens has a significant effect on Cu II affinity (assuming that the amide p K a is strongly correlated with the amine p K a of the source amino acid). However, due to the high amide p K a values (>15) they are not measurable by experimental titration . Nevertheless, based on the discussion presented above, one may propose that positively charged and/or H‐bond donor side chains could interact with the amide carbonyl oxygen, hence decreasing the peptide group p K a (Figure C).…”
Section: The Two Motifs and Metal Ions They Bindmentioning
confidence: 99%
“…[19][20][21][22] In this paper, we showed that different transition metal ions in solution can be distinguished by using the transient quenching events generated by binding of the metal ions. For example, Taraska et al showed that fluorescence of organic dye is quenched by transition metal ion binding to a nearby site, and several similar works have followed.…”
Section: Articlementioning
confidence: 99%